A Novel Diffuse Fraction‐Based Two‐Leaf Light Use Efficiency Model: An Application Quantifying Photosynthetic Seasonality across 20 AmeriFlux Flux Tower Sites. (21st October 2017) - Yan, Hao; Wang, Shao‐Qiang; Yu, Kai‐Liang; Wang, Bin; Yu, Qin; Bohrer, Gil; Billesbach, Dave; Bracho, Rosvel; Rahman, Faiz; Shugart, Herman H.
Abstract: Diffuse radiation can increase canopy light use efficiency (LUE). This creates the need to differentiate the effects of direct and diffuse radiation when simulating terrestrial gross primary production (GPP). Here, we present a novel GPP model, the diffuse‐fraction‐based two‐leaf model (DTEC), which includes the leaf response to direct and diffuse radiation, and treats maximum LUE for shaded leaves ( ɛ msh defined as a power function of the diffuse fraction ( D f )) and sunlit leaves ( ɛ msu defined as a constant) separately. An Amazonian rainforest site (KM67) was used to calibrate the model by simulating the linear relationship between monthly canopy LUE and D f . This showed a positive response of forest GPP to atmospheric diffuse radiation, and suggested that diffuse radiation was more limiting than global radiation and water availability for Amazon rainforest GPP on a monthly scale. Further evaluation at 20 independent AmeriFlux sites showed that the DTEC model, when driven by monthly meteorological data and MODIS leaf area index (LAI) products, explained 70% of the variability observed in monthly flux tower GPP. This exceeded the 51% accounted for by the MODIS 17A2 big‐leaf GPP product. The DTEC model's explicit accounting for the impacts of diffuse radiation and soil water stress along with its parameterization for C4 and C3 plants was responsible for this difference. The evaluation of DTEC at Amazon rainforest sites demonstrated its potential to capture the unique seasonality of higher GPP during the diffuse radiation‐dominated wet season. Our results highlight the importance of diffuse radiation in seasonal GPP simulation. Plain Language Summary: As diffuse radiation can increase canopy light use efficiency (LUE), there is a need to differentiate the effects of direct and diffuse radiation in simulating terrestrial gross primary production (GPP). A novel diffuse‐fraction (Df)‐based two leaf GPP model (DTEC) developed by this study considers these effects. Evaluation at 20 independent flux tower sites using the MOD15 LAI product finds that the DTEC model explains 71% of the variability observed in monthly flux GPP. Evaluation at two Amazonian tropical forest sites (KM67 and KM83) indicates this model's potential to capture the unique seasonality in GPP, e.g., higher GPP in diffuse radiation‐dominated wet season, while the two‐leaf LUE GPP model ( He et al ., 2013) cannot due to using constant LUE for sunlit and shaded leaf. The DTEC model initially simulated the linear relationship between canopy LUE and D f found at Amazon KM67 and KM83 forest sites. It shows a positive response of forest GPP to the atmosphere diffuse radiation in Amazon. Diffuse radiation was more limiting than global radiation and water for Amazon forest GPP on a seasonal scale. This differs from results of recent studies in which light‐controlled leaf phenology plays the dominant role in seasonal variation of GPP in Amazonian. Key Points: A diffuse fraction based two leaf GPP model is developed Capture the unique seasonality in Amazon rainforest GPP, e.g., higher GPP in diffuse radiation‐dominated wet season Diffuse radiation is more limiting than global radiation and water for Amazon rainforest GPP on a seasonal scale